Maternal gestational diabetes mellitus and risk of allergic diseases in offspring - Min-Che Hsu; Chien-Heng Lin; Ming-Chih Lin (Pediatrics and Neonatology)
Background: Gestational diabetes mellitus has been linked to inflammation, immune dysregulation in offspring, and changes in the microbiota. It may have long-term implications for the health of children. The aim of this study was to determine if gestational diabetes mellitus increases the risk of allergic diseases in offspring. Methods: The data source was the National Health Insurance Research Database (NHIRD) of Taiwan. The pairing of mothers and children was established by connecting the NHIRD with the Taiwan Maternal and Child Health Database. First-time pregnant mothers between 2004 and 2019 were enrolled. The GDM group consisted of 22,741 cases. The control group was selected from individuals without GDM matched by maternal age, neonatal gender, and neonatal birthdate at a ratio of 1–4. The primary endpoint was the incidence of childhood allergic diseases, such as asthma, allergic rhinitis, atopic dermatitis, and urticaria. The secondary endpoint was the risk associated with the development of allergic diseases in offspring, considering the presence or absence of insulin therapy. Results: The development of allergic rhinitis, atopic dermatitis, and urticaria were found to be significantly associated with GDM. However, no significant association was observed between GDM and asthma. GDM control without insulin was associated with an increased risk of developing allergic rhinitis, urticaria, and atopic dermatitis. However, in the group receiving insulin treatment, there was no significant elevation in the risk of any allergic diseases. Conclusion: GDM may elevate the risk of certain atopic diseases in offspring, such as allergic rhinitis, atopic dermatitis, and urticaria.